The effect of increasing financial incentives in a panel survey: an experiment on the British Household Panel Survey, Wave 14 - Heather Laurie (University of Essex, Institute for Social and Economic Research (ISER), 2007)
This descriptive paper reports the results of an experiment carried out at wave 14 (2004) of the British Household Panel Survey (BHPS). A split-sample design was used to assess the effect on response rates of increasing the monetary incentive given to survey respondents from 7 per interview to 10 per interview. The results suggest that even though the increase was relatively small, response rates were higher for those receiving the increased incentive amount, an effect that varied by the demographic characteristics and previous response history of respondents.
Keywords: 330